2017
DOI: 10.1002/jcp.25960
|View full text |Cite
|
Sign up to set email alerts
|

Leucine elicits myotube hypertrophy and enhances maximal contractile force in tissue engineered skeletal muscle in vitro

Abstract: The amino acid leucine is thought to be important for skeletal muscle growth by virtue of its ability to acutely activate mTORC1 and enhance muscle protein synthesis, yet little data exist regarding its impact on skeletal muscle size and its ability to produce force. We utilized a tissue engineering approach in order to test whether supplementing culture medium with leucine could enhance mTORC1 signaling, myotube growth, and muscle function. Phosphorylation of the mTORC1 target proteins 4EBP‐1 and rpS6 and myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Cross-linking of fibrin with FXIII significantly impeded force generation (189 ± 64 μN/mm 2 ). The forces we report here are in the same range as what we and others previously reported ( Huang et al, 2005 ; Brady et al, 2008 ; Vandenburgh et al, 2008 ; Fuoco et al, 2015 ; Madden et al, 2015 ; Martin et al, 2017 ; Kasper et al, 2018 ). Forces exerted by excised tibialis anterior muscle were around 1–2 mN ( Cook et al, 2016 ), thus the forces we obtain are only slightly lower.…”
Section: Discussionsupporting
confidence: 90%
“…Cross-linking of fibrin with FXIII significantly impeded force generation (189 ± 64 μN/mm 2 ). The forces we report here are in the same range as what we and others previously reported ( Huang et al, 2005 ; Brady et al, 2008 ; Vandenburgh et al, 2008 ; Fuoco et al, 2015 ; Madden et al, 2015 ; Martin et al, 2017 ; Kasper et al, 2018 ). Forces exerted by excised tibialis anterior muscle were around 1–2 mN ( Cook et al, 2016 ), thus the forces we obtain are only slightly lower.…”
Section: Discussionsupporting
confidence: 90%
“…Pioneering studies by Shah et al (2000) demonstrated that leucine supplementation in rats is able to markedly stimulate protein synthesis in skeletal muscle, activating the mTOR intracellular signaling pathway. Martin et al (2017) observed in a cell culture model of skeletal muscle tissue that leucine improves mTOR signaling, associated with microtubule hypertrophy and increased maximal contractile force by electrical stimulation, providing evidence for the efficacy of leucine as an anabolic nutritional agent which may influence the functional capacity of muscle.…”
Section: Introductionmentioning
confidence: 95%
“…For example, electrical and mechanical stimulation can induce tissue maturation, increasing myosin heavy chain expression and myoblast differentiation in vitro (Niu et al, 2013;Player et al, 2014), as well as other tissue maturation benefits, i.e. improved metabolic flux, increased Ca 2+ transient amplitude, tetanic force and fatigue resistance (Davis et al, 2019;Khodabukus et al, 2019;Martin et al, 2017;Mills et al, 2019;Takahashi et al, 2018). These simulated 'exercise protocols' have greatly increased myotube width and force (Powell et al, 2002;Raman et al, 2016).…”
Section: D Human Cell Culture Modelsmentioning
confidence: 99%